Influence of indicators for thiotriazolin phagocytic activity of leukocytes in the blood in the later period of development of stomach ulcers against pneumonia - Furdychko, L. O. (Journal of Education, Health and Sport, 2017)
Important for the pathogenesis of pneumonia and gastric ulcers should state phagocytic activity of leukocytes (PHAL) in the blood. In fact the state of nonspecific resistance factors to some extent depends on the disease, the development of complications, prognosis and therapy. Materials and methods. The study was conducted on 49 male guinea pigs. The experimental pneumonia caused by the method Shlyapnykova V. N., Solodova T. L., gastric ulcer simulated method Komarov V. I. Nonspecific resistance of animals we evaluated, examining the phagocytic activity of leukocytes (PHAL), nitroblue tetrazolium test (NST- test). Phagocytic activity of leukocytes (PHAL) in blood were studied in terms phagocytic index (PHI) and the phagocytic number (PHN) and determined by the method Menshikov V. V. NST - test method Vyksmana M. E., Mayanskoho A. H. The figures research results processed by statistical method Student. Results and discussion. For the experiment, we selected two models of disease: experimental pneumonia (EP) and peptic ulcer (PU). State PHAL determined by the level of phagocytic number (PHN), phagocytic index (PHI), NST-test levels in the ЕP+ PU. Found that in the 10-th and 18-th day of development of pathological process both in the stomach and the lungs of guinea pigs, there was reduction of PHI respectively 15,8% (P <0,05) and 21,5% (P <0.05) relative to controls, indicating inhibition of phagocytic activity of leukocytes. Research phagocytosis next marker - phagocytic number (PHN) in the blood also showed its decline in the 10-th and 18-th day of EP + PU respectively 16,7% (P <0,05) and 23,2% (P <0 , 05) against the first group of animals. Studied at the cellular level of organization NST-test as a measure of metabolic activity of neutrophils in experimental pneumonia and stomach ulcers. Research NST-test 10 days EP+ PU established its reduction in blood at 18,5% (P <0,05), and after 18 days the formation of inflammation in the lungs and stomach ulcer, this marker suffered further decay - decreased by 29,8% (P <0,05). To correct the results obtained was used thiotriasolin drug. After application of the drug substance PHAL markers in the blood of animals on the 18th day of the experiment increased compared to animals on the same day, which was put thiotriasolin. Indexes and PHI and PHN increased respectively by 12,3% (P <0,05), and 14,2% (P <0,05), and the level of NST-test increased by 16,8% (P <0,05).Conclusions. Thiotriazoline use during EP + PU causes the growth of individual indicators PHAL.